2009
DOI: 10.1523/jneurosci.5118-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Musical Training Shapes Structural Brain Development

Abstract: The human brain has the remarkable capacity to alter in response to environmental demands. Training-induced structural brain changes have been demonstrated in the healthy adult human brain. However, no study has yet directly related structural brain changes to behavioral changes in the developing brain, addressing the question of whether structural brain differences seen in adults (comparing experts with matched controls) are a product of "nature" (via biological brain predispositions) or "nurture" (via early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
585
5
27

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 753 publications
(650 citation statements)
references
References 62 publications
33
585
5
27
Order By: Relevance
“…It has been suggested that musicians exhibit distinct auditory (42,43), verbal (44), and broad cognitive (45) abilities and/or systems. In particular, musical training, whether singing or playing an instrument, requires developing perception-action coordination, which may promote unusually strong connections between perception and action systems in the brain (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that musicians exhibit distinct auditory (42,43), verbal (44), and broad cognitive (45) abilities and/or systems. In particular, musical training, whether singing or playing an instrument, requires developing perception-action coordination, which may promote unusually strong connections between perception and action systems in the brain (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, musicians -experts in the musical domain-exhibit functional and structural changes in the brain, what also has driven music into a device for studying brain plasticity (Hyde, Lerch, Norton, Forgeard, Winner, & Evans, 2009;Schlaug, 2006;Münte, Altenmüller, & Jäncke, 2002).…”
Section: Cognitive Neuroscience Of Musicmentioning
confidence: 99%
“…Musicians are an ideal population to investigate the neuroanatomical underpinnings of exceptional sensorimotor skills (Schlaug 2001;Munte et al 2002;Hyde et al 2009;Herholz and Zatorre 2012;Luo et al 2012). Some researchers have shown specialized anatomical and functional features within musician groups (Elbert et al 1995;Bangert and Schlaug 2006), which have been used to support the interpretation that specialized long-term skill training of particular instruments can lead to instrumentspecific adaptations (Stewart 2008).…”
Section: Introductionmentioning
confidence: 99%